PEMBERDAYAAN UMAT MELALUI BANK SHARIAâH - Marjudo, Abd. Basyir (Hunafa: Jurnal Studia Islamika, 2008)
One of the Indonesian Muslimsâ attempts to empower the Islamic society in the aspect of economy is to establish Islamic bank.Â  The purpose of this bank is to enhance the prosperity of the Islamic society who does not wish to use conventional banks employing interest system. The reason is that bank interest, according to them, is identical to riba. Therefore, they avoid using conventional banks employing Â interest system, and use Islamic banks, instead.Kata Kunci : pemberdayaan ekonomi, bank sharâiah,